2019
DOI: 10.21614/chirurgia.114.4.467
|View full text |Cite
|
Sign up to set email alerts
|

A Study Comparing Outcomes of Appendectomy between HIV-Infected and HIV-Negative Patients

Abstract: Complicaţiile postoperatorii (44,4% faţă de 17,2%, P = 0,03) şi durata mai lungă a internării în spital (7,28 zile faţă de 5,95 zile, P = 0,004) au fost de asemenea mai frecvent observate la pacienţii cu HIV +. Nu au existat diferenţe în ceea ce priveşte ratele de ruptură ale apendicelui, rezultatele histopatologice şi mortalitatea. Concluzii: Pacienţii HIV+ s-au prezentat mai târziu la spital, iar intervenţia chirurgicală a fost asociată cu o rată mai ridicată a morbidităţii postoperatorii şi o perioadă mai l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Blumberg's sign was present in 90% of cases in our study the defense of the right iliac fossa was present in 96.7%. This defense of the right iliac fossa has been found in all series [11] [16].…”
Section: Physical Signsmentioning
confidence: 64%
“…Blumberg's sign was present in 90% of cases in our study the defense of the right iliac fossa was present in 96.7%. This defense of the right iliac fossa has been found in all series [11] [16].…”
Section: Physical Signsmentioning
confidence: 64%
“…The causative agents including mycobacterium, cytomegalovirus, cryptosporidium, pneumococcus, Amoebic appendicitis, Pill Impaction and IRIS have been reported as AA in HIV patients. 6,[13][14][15] There are different conditions in HIV patients which can present as abdominal pain or right iliac fossa pain. For instance, disseminated histoplasmosis and Kaposi's Sarcoma can present as AA.…”
Section: Hiv and Appendicitismentioning
confidence: 99%
“…10 In other studies, no difference was seen in the complication rate, length of hospital stays, and mortality between HIV-positive and HIV-negative patients. 11,13 In one case study, pill impaction was found in appendiceal orifice with HIV patient. 14 In summary, it is possible that HIV can influence the appendix in different ways: (1) HIV virus directly affects the appendix, (2) opportunistic infections, (3) IRIS and (4) high levels of perioperative complications.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…As this patient population grows, more such patients will undergo surgery. Patients with HIV are generally immunocompromised, and HIV infection is regarded as a perioperative risk associated with higher morbidity, more severe postoperative complications, and longer hospital stays [ 2 5 ]. Thus, surgeons must assess HIV-positive [HIV (+)] patients carefully to predict their postoperative risk and evaluate the benefit–risk balance of surgery.…”
Section: Introductionmentioning
confidence: 99%